ANALISIS PARTISIPASI MASYARAKAT DAN PEMERINTAH DAERAH DALAM PENGEMBANGAN SEKTOR PARIWISATA BUKIT LAWANG KECAMATAN BAHOROK - M. Avizal Ramadhan; Imsar Imsar (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to find out and see how the role of society and local government participation in the development of the tourism sector in Bukit Lawang. This research uses qualitative method with research noted during field observation and interviews conducted by the author to informants. Sample in this study used a puposive sampling technique while attention to the availability of the society to become research informants. The result of this study indicate that the current development if the Bukit Lawang tourist attraction shows the local government is not optimal gave attention to the potential of Bukit Lawang. Including first, the road infrastructure to Bukit Lawang still verry bad. Second, there is no availability of facilities. Third, the lack of implementation of education and training at the Langkat Regency tourism office for the development of human resources in the tourism sector. Forth, the lack of cooperation between the local government and the community to hold meetings both formally and informally with the aim of developing Bukit Lawang. Fifth, lack of regular guidance and supervision in the field by the Langkat district tourism. Keywords : Participation, Society, Local Government, Tourism Development.